EFFECT OF CANE PAYMENT ON SUGAR QUALITY AND TORULA'S INVESTMENT EFFICIENCY - Ruano Bormey, Meliza M.; González Suárez, Erenio; León Chirino, Erick Ariel; de la Cruz Martínez, Leidys; Albernas Carvajal, Yailet (Centro Azúcar Journal, 2022)
Introduction: In order to improve the quality of raw sugar in the sugar industry and to increase the investment efficiency related to the alternative production of torula yeast, an analysis of the effect and cost of cane payment for its quality is carried out. This is determined, by the results obtained in the laboratory, from the calculation of the yield per cane (RPC). Objective: To determine the effect of cane payment on raw sugar quality and on the investment efficiency of a torula yeast plant in two Cuban sugar mills A and B. Materials and Methods: The global process modeling method is used by means of matrix aggregation of the models of the technological processes’ stages of raw sugar and final molasses production, in two different industrial facilities, using Statgraphics Centurion Software. The evaluation of alternatives of per cent extraction of the juice from the filters in the investments is included. Results and Discussion: When analyzing two types of sugarcane, it is observed that increasing its quality improves both the levels of raw sugar production and the brix of the final honey. This raises profits in the yeast plant in both sugar mills. Conclusions: The importance of cane payment for its quality was demonstrated by increasing the profits of the yeast plant and the sugar mill by1604101.69 USD/year, which exceeds the increase in cane payment, which is 447210.44 USD/year.